FROM RISK TO SAFETY: AI'S PROMISE FOR INDIA'S ROAD SAFETY - Nishchay Mahori,; Amita Mahor,; Yogesh Mahor, (IJRDO-Journal of Applied Science, 2024)
India’s road safety scenario presents several critical challenges, evidenced by persistently high rates of accidents and fatalities despite concerted efforts to improve infrastructure and enforcement mechanisms. In 2022 alone, India accounted for 12% of global road fatalities, with the economic toll amounting to 4% of the nation’s GDP. This paper delves into the transformative potential of Artificial Intelligence (AI) in bolstering road safety across the country. It explores key AI applications such as predictive analytics to identify high-risk areas, AI-powered traffic management systems to optimize traffic flow, automated license plate recognition to enhance enforcement efficiency, and intelligent emergency response systems to ensure rapid assistance in case of accidents.Through case studies from Tamil Nadu and Karnataka, complemented by international examples, the paper demonstrates the efficacy of AI in reducing accidents and improving traffic management. The study identifies significant gaps, including the absence of a comprehensive regulatory framework, inadequate data sharing mechanisms, and concerns regarding data privacy. It provides recommendations to address these issues, emphasizing the need for robust regulations for AI adoption, fostering collaboration among industry experts, academia, and policymakers, and addressing resource constraints.By implementing these targeted policy decisions, GoI can harness AI to achieve a vision of zero accidents, thereby significantly enhancing road safety, reducing costs, and saving lives. The urgency to act is paramount, as AI provides a vital pathway towards creating a safer and more efficient transportation ecosystem in India.